2011
DOI: 10.1007/s13592-011-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell comb does not control Varroa mites in colonies of honeybees of European origin

Abstract: -We tested the idea that Varroa destructor can be controlled in colonies of the European subspecies of Apis mellifera by providing them with combs built of small cells, in which immature mites might have difficulty developing for lack of space. We established seven pairs of equal-size colonies that started out equally infested with mites. In each pair, one hive contained only standard-cell (5.4 mm) comb, and the other contained only small-cell (4.8 mm) comb. We measured the colonies' mite loads at monthly inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 9 publications
7
17
1
Order By: Relevance
“…Further, a reduced bee developmental time (Buchler and Drescher 1990;Moritz and Jordan 1992;Rosenkranz and Engels 1994) and reduced comb cell size (Message and Goncalves 1995;Medina and Martin 1999;Piccirillo and De Jong 2004) can reduce the ability of mother mites to produce viable mated female offspring before the adult bee emerges from the cell. However, Seeley and Griffin (2011) have clearly demonstrated that small comb cell size did not reduce Varroa mite infestations for European races of A. mellifera . Climate has also been suggested to play a role in reduced mite infestation (Moretto et al 1991b).…”
Section: A M Scutellata In Brazil and South Africamentioning
confidence: 87%
See 1 more Smart Citation
“…Further, a reduced bee developmental time (Buchler and Drescher 1990;Moritz and Jordan 1992;Rosenkranz and Engels 1994) and reduced comb cell size (Message and Goncalves 1995;Medina and Martin 1999;Piccirillo and De Jong 2004) can reduce the ability of mother mites to produce viable mated female offspring before the adult bee emerges from the cell. However, Seeley and Griffin (2011) have clearly demonstrated that small comb cell size did not reduce Varroa mite infestations for European races of A. mellifera . Climate has also been suggested to play a role in reduced mite infestation (Moretto et al 1991b).…”
Section: A M Scutellata In Brazil and South Africamentioning
confidence: 87%
“…Morphological differences were observed with Arnot Forest bees having a smaller body size, more similar to Africanized bees, than typical European honeybees (Mikheyev et al 2015). This could mean a shorter developmental duration or inadequate cell space for mite reproduction in the Arnot Forest bees, even though these characteristics are not enough to fully support mite resistance (Martin 1998;Seeley and Griffin 2011).…”
Section: Arnot Forest Ithaca Ny Usamentioning
confidence: 97%
“…Erickson et al (1990) claimed that alterations of the comb cell width induced changes in the worker body size without selection and breeding. However, contradictory conclusions were formulated by McMullan and Brown (2006) and Seeley and Griffin (2011). McMullan and Brown (2006) found that a 7-8% reduction of comb cell width resulted in an only 1% decrease in the head and thorax width.…”
Section: Introductionmentioning
confidence: 99%
“…Martin & Kryger [114] found evidence in support of this hypothesis when they compared the number of offspring per cycle of Varroa in brood of A. m. scutellata with that in brood of the larger A. m. capensis bees in A. m. scutellata cells. Seeley and Griffin [115] compared bees of the same origin that were either placed on frames with small (4,8 mm) or large (5,4 mm) cells. They measured population development of Varroa once a month-from mid-June to mid-October and did not find differences in population growth of the mites.…”
Section: Population Growth Of Varroamentioning
confidence: 99%